AN INVESTIGATION INTO PRICING TECHNIQUES OF FLEA MARKET OPERATORS IN ZIMBABWE: CASE STUDY OF BINDURA (2015). - Felix, Chari; Zivanai, Onias (IJRDO - Journal of Business Management, 2016)
The study was aimed at investigating the pricing techniques of Flea Market Operators in Zimbabwe; using Bindura Town based Flea Market operators as a case study. The main objectives of the study were to identify pricing strategies, identifying the competitive edges of Flea market operators and to find out how traders ensure that their selling prices are viable. Questionnaires, Interviews and Observation where used as primary data gathering tools. Findings revealed that a plethora of pricing techniques was used to set selling prices but the chief method was competition based pricing technique. The major recommendations of the study were that Flea market operators should attain elementary theoretical knowledge of pricing and that they should maintain basic business records so that they can assist in setting viable prices.